Alternatives to Antibiotics: A Symposium on the Challenges and Solutions for Animal Health and Production - Callaway, Todd R.; Lillehoj, Hyun; Chuanchuen, Rungtip; Gay, Cyril G. (Antibiotics (Basel), 2021)
Antibiotics have improved the length and quality of life of people worldwide and have had an immeasurable influence on agricultural animal health and the efficiency of animal production over the last 60 years. The increased affordability of animal protein for a greater proportion of the global population, in which antibiotic use has played a crucial part, has resulted in a substantial improvement in human quality of life. However, these benefits have come with major unintended consequences, including antibiotic resistance. Despite the inherent benefits of restricting antibiotic use in animal production, antibiotics remain essential to ensuring animal health, necessitating the development of novel approaches to replace the prophylactic and growth-promoting benefits of antibiotics. The third International Symposium on “Alternatives to Antibiotics: Challenges and Solutions in Animal Health and Production” in Bangkok, Thailand was organized by the USDA Agricultural Research Service, Faculty of Veterinary Science, Chulalongkorn University and Department of Livestock Development-Thailand Ministry of Agriculture and Cooperative; supported by OIE World Organization for Animal Health; and attended by more than 500 scientists from academia, industry, and government from 32 nations across 6 continents. The focus of the symposium was on ensuring human and animal health, food safety, and improving food animal production efficiency as well as quality. Attendees explored six subject areas in detail through scientific presentations and panel discussions with experts, and the major conclusions were as follows: (1) defining the mechanisms of action of antibiotic alternatives is paramount to enable their effective use, whether they are used for prevention, treatment, or to enhance health and production; (2) there is a need to integrate nutrition, health, and disease research, and host genetics needs to be considered in this regard; (3) a combination of alternatives to antibiotics may need to be considered to achieve optimum health and disease management in different animal production systems; (4) hypothesis-driven field trials with proper controls are needed to validate the safety, efficacy, and return of investment (ROI) of antibiotic alternatives.